2014
DOI: 10.1038/hr.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between red-cell distribution width and abnormal left ventricle geometric patterns in patients with untreated essential hypertension

Abstract: Abnormal left ventricle (LV) geometric patterns are associated with an increased risk of vascular complications of hypertension (HT). The association between red-cell distribution width (RDW) and HT has been recently investigated; however, the relationship between abnormal LV geometric patterns and RDW has not been studied before. The aim of this study was to investigate the relationship between RDW and abnormal LV geometric patterns in patients with untreated essential HT. Measurements were obtained from 139 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…This study also indicates an association between RDW and LVH and affirms the importance of this index in the full evaluation of hypertensive patients. We noticed that a similar study conducted by Kilicaslan et al had been published in the Hypertension Research [ 25 ]. In this study four different geometric patterns (Normal geometry, concentric remodeling, eccentric hypertrophy, concentric hypertrophy) were determined according the LVMI, and they found that LV geometry type were independent associated with high RDW.…”
Section: Discussionmentioning
confidence: 57%
“…This study also indicates an association between RDW and LVH and affirms the importance of this index in the full evaluation of hypertensive patients. We noticed that a similar study conducted by Kilicaslan et al had been published in the Hypertension Research [ 25 ]. In this study four different geometric patterns (Normal geometry, concentric remodeling, eccentric hypertrophy, concentric hypertrophy) were determined according the LVMI, and they found that LV geometry type were independent associated with high RDW.…”
Section: Discussionmentioning
confidence: 57%
“…Kilicaslan et al . recently demonstrated that RDW values were associated with ventricular geometrical patterns [ 23 ] in untreated hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell distribution width (RDW), which is a readily available parameter in complete blood cell counts (CBC), has been conventionally used for the evaluation of heterogeneity of circulating erythrocytes and differential diagnosis of anemia . However, recent studies have found that increased RDW also shows promising predictive value for many diseases with high mortality, such as hypertension, myocardial infarction, coronary heart disease, heart failure, sepsis, and acute pancreatitis . Although the underlying biological and metabolic mechanism of increased RDW has not been validated, the association between higher RDW and higher mortality risk in many diseases indicates that the clinical significance of RDW should be broadened.…”
Section: Introductionmentioning
confidence: 99%